Ankylosing spondylitis and central core disease: case report - Rosana Herminia Scola; Kátia Lin; Fábio Massaiti Iwamoto; Walter Oleschko Arruda; Lineu Cesar Werneck (Arquivos de Neuro-Psiquiatria)
Ankylosing spondylitis (AS) is an inflammatory disorder of unknown cause that primarily affects the axial skeleton. Neurological manifestations of AS are usually related to spinal deformities. Previous studies of the paraspinal muscles of AS patients showed muscle fiber atrophy, and core fibers. On the other hand, central core disease (CCD) is a genetic condition that primarily involves the skeletal muscles, but can present articular deformities secondary to muscular weakness. We report the case of a 45-year-old man with clinical and radiological diagnosis of AS and proximal muscular weakness in the lower limbs. Needle electromyography showed myopathic features and nerve conduction study was normal. Muscle biopsy disclosed almost complete predominance of type-1 fibers, and fibers with central cores. This is the first report of AS and CCD. Whether central core myopathy is coincidental or a new association with AS is discussed.